Workshop Pelatihan Pengembangan Perangkat Project Based Learning dalam Pembelajaran IPA se-Kota Maros - Ramlawati Ramlawati; Rifda Nur Hikmahwati Arif; Salma Samputri; Sitti Saenab; Sitti Rahma Yunus (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2023)
One way that teachers can realize the success of learning in training students to be independent and able to think creatively is by choosing a learning model that suits the learning material. One of the learning models that can improve students' creative thinking is the Project Based Learning (PjBL) model. The PjBL model is also one of the recommended models in independent curriculum learning. The project-based learning model is an innovative learning that is student centered and places the teacher as a motivator and facilitator, where students are given the opportunity to work autonomously to construct their learning Educators must be able to develop learning tools as one of the keys in establishing a learning system in accordance with the objectives of the learning itself. However, most teachers, especially science teachers in Maros City, are still lacking in understanding about PjBl tools and the syntax of PjBL itself. Therefore, a training or workshop on Project Based Learning Device Development in Science Learning in Maros City was held.